Economic growth and carbon dioxide emission in Nigeria (2021)
Environmental degradation measured by CO2 emissions is a significant challenge to sustainable economic development. Owing to the significant impact of the empirical relationship between economic growth and CO2 emissions, this study examined the relationship between economic growth and carbon dioxide emission with a view to testing the validity or otherwise of the Environmental Kuznets Curve (EKC) in Nigeria. Using Autoregressive Distributed Lags (ARDL) approach, the study employed data on trade openness, electricity consumption, population and the square of GDP as control variables in the analysis for the period 1970 to 2018. The result showed that electricity consumption and trade openness have a negative and significant relationship with CO2 emission, while population growth has a positive but insignificant impact on CO2 emission. This insignificant impact of population growth can be linked to the lower income of the populace. However, the estimated coefficient of the square of income is negative, while that of its level is positive and thus supports the existence of EKC in Nigeria. Increasing the degree of openness to international trade along with appropriate trade policies will contribute to the Nigerian economy as openness leads to the reduction of pollutants in the environment. Adoption of mixed energy consumption, especially through hydroelectricity and solar system, will drastically reduce the rate of carbon emission in Nigeria regarding the fact that Nigeria is well endowed with these resources.